Multidisciplinary Approach to Osteoporosis From Assessment to Treatment (Springer International Publishing, 2018)
This book describes in detail the multidisciplinary management of osteoporosis, providing readers with a thorough understanding of the rationale for a multidisciplinary approach and with the tools required to implement it effectively. The emphasis is on a translational approach, starting from basic concepts and fundamental mechanisms of the pathology and clinical morbidity. Experts in the field discuss the full range of relevant topics, including the significance of physical activity, nutritional strategies, and pharmacological treatment. Put another way, the book covers all aspects from the bench to the bedside. Physicians, scientists, and postgraduate students will all find it to be invaluable in understanding the causes and optimal management of osteoporosis, the incidence of which is increasing rapidly as populations age.